2017
DOI: 10.14639/0392-100x-1243
|View full text |Cite
|
Sign up to set email alerts
|

Utricular hypofunction in patients with type 2 diabetes mellitus

Abstract: L’obiettivo di questo studio è stato quello di valutare la funzione utricolare e la funzione dei canali semicircolari laterali in pazienti con diabete mellito di tipo 2, con o senza cadute, afferenti all’assistenza sanitaria di base. Sono stati arruolati 101 pazienti con diabete mellito di tipo 2 (26 con storia di cadute, 75 senza), di età compresa tra 34 e 84 anni, e 51 volontari sani di età compresa tra 40 e 83 anni, i quali hanno negato vertigini, capogiri, instabilità, ipoacusia o disordini neurologici. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…It has been reported that the occurrence of BPPV was higher in people with type 2 diabetes (46%) compared to those without the metabolic disease (37%). 92 In a recent report, Jáuregui-Renaud et al 94 studied the function of horizontal SCCs and utricle in patients with type 2 diabetes, who did not have any history of dizziness or other vestibular symptoms. The authors found that the patients had downsized…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the occurrence of BPPV was higher in people with type 2 diabetes (46%) compared to those without the metabolic disease (37%). 92 In a recent report, Jáuregui-Renaud et al 94 studied the function of horizontal SCCs and utricle in patients with type 2 diabetes, who did not have any history of dizziness or other vestibular symptoms. The authors found that the patients had downsized…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the occurrence of BPPV was higher in people with type 2 diabetes (46%) compared to those without the metabolic disease (37%). 92 In a recent report, Jáuregui-Renaud et al 94 studied the function of horizontal SCCs and utricle in patients with type 2 diabetes, who did not have any history of dizziness or other vestibular symptoms. The authors found that the patients had downsized responses to unilateral centrifugation compared to healthy volunteers, but their responses to horizontal SCC stimulation were similar and they had also a larger sway area and a lengthier sway path in the test of posturography.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the otolith received more attention than the SCCs, and SCC assessments were across a range of frequencies (low, middle, high; Table 2 ) ( 17 ) in people with Type 2 DM. Specifically, 10/11 studies detected some form of otolith dysfunction ( 43 , 45 53 , 57 ), and 4/7 studies identified SCC dysfunction ( 40 , 48 , 49 , 52 54 , 56 ). While one study did not report DM type and another did not differentiate between types ( 37 , 38 ), two studies compared classes of DM; demonstrating similarity in high frequency SCC testing (passive/active head thrust, video head impulse testing: vHIT) between people with Type 1 and 2 ( 40 , 56 ).…”
Section: Human Studiesmentioning
confidence: 99%
“…Female representation ranged from 8%–88%, but more often ranged between 30% and 60%. BMI was only reported in 6/23 reviewed studies ( 46 , 49 , 54 , 56 , 57 ). While the importance of age is implicitly recognized by authors who matched or controlled for age within designs, we are unaware of studies directly considering the possible interaction of age and DM with vestibular function.…”
Section: Human Studiesmentioning
confidence: 99%
“…There is growing attention paid to the relationship between diabetes and inner ear structures. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] In particular, there is a wealth of evidence suggesting that hearing loss (HL) may be a disabling complication of diabetes mellitus (DM) [ 26 , 27 ]. The consequences of DM affecting the ear can include the ability to understand speech, the risk of falling, and the onset of tinnitus, with concerns ranging from a lowered quality of life to an increase in mortality.…”
Section: Introductionmentioning
confidence: 99%